Are “outsiders” in? Exploring the impact of outsourced workers’ perceived insider status and job value status on job performance - Yang, Jean Fan; Shi, Wei; Chen, Erica Wen; Luo, Ben Nanfeng; Zhao, Jenny Zejun; Yin, Zhechen; Tao, Jiaqi (Frontiers in Psychology, 2023)
The outsourcing of human resources, a typical form of flexible employment, describes the situation in which employees are hired by one entity (often known as an agency or contractor) but conduct work in another organization (known as a client organization). Studies are increasingly focusing on the influences of human resources outsourcing on corporate performance; however, its psychological experience and behavioral outcomes at the employee level, particularly in how outsourced employees differ from their standard co-workers, are under-researched. Drawing on social categorization theory, we propose that relative to standard employees, outsourced employees perceive themselves less as organizational insiders and therefore demonstrate lower job performance. We further draw on the human resource architecture model and argue that employees' objective job value status (core versus peripheral) moderates their subjective status perception such that the differences of perceived insider status and subsequent job performance between outsourced and standard employees are greater among the core-status than peripheral-status category. We undertook a two-stage multi-source study and found support for our hypothesized moderated mediation model via the questionnaire responses of 147 outsourced employees, 279 standard employees, and their immediate supervisors. Our findings were further supported by interviews with 31 workers, their supervisors, and human resources personnel. Together, we improve understanding of how employment forms and workers' job values influence individuals' perceived insider status and job performance. Our contributions to the literature on nonstandard employees, human resource architecture, broader employment-job matching, and implications for managerial practices are also highlighted.